2008
DOI: 10.1002/chem.200701650
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Remarkable Biological Properties of Cyclodextrins Bearing Guanidinoalkylamino and Aminoalkylamino Groups on Their Primary Side

Abstract: The introduction of aminoalkylamino and guanidinoalkylamino substituents on the primary side of beta- and gamma-cyclodextrin (CDs) resulted in a series of novel compounds that were extensively characterized by NMR spectroscopy and mass spectrometry. Bromination of the primary side of beta- and gamma-CD, and reaction with neat alkylene diamines at a pressure of 7 atm afforded aminoalkylamino derivatives that were then guanylated at the primary amino group to give the corresponding guanidinoalkylamino-CDs. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 115 publications
1
49
0
3
Order By: Relevance
“…Interestingly, the transfection efficiency of these vectors against human embryonic kidney HEK 293T cells favorably compared with that of the commercial cationic lipid formulation Lipofectamine 2000 . [61] Reineke and co-workers took advantage of the copper(I)-catalyzed Huisgen 1,3-dipolar azide-alkyne cycloaddition reaction [62] between the per-(O-2,O-3)-acetylated heptaazide 27 and acriloyl amide derivatives to synthesize a family of polycationic b-CD "click clusters" (28) bearing seven linear oligoethyleneimine branches with variable, but controlled, number of protonable amino groups (Scheme 5). [63] Agarose gel electrophoresis, DLS, and TEM experiments revealed that the click polycations complexed pDNA and protected it from nuclease degradation by forming nanoparticles with an average diameter of 80-130 nm.…”
Section: Polycationic Cyclodextrins-pdna Complexes (Cdplexes)mentioning
confidence: 99%
“…Interestingly, the transfection efficiency of these vectors against human embryonic kidney HEK 293T cells favorably compared with that of the commercial cationic lipid formulation Lipofectamine 2000 . [61] Reineke and co-workers took advantage of the copper(I)-catalyzed Huisgen 1,3-dipolar azide-alkyne cycloaddition reaction [62] between the per-(O-2,O-3)-acetylated heptaazide 27 and acriloyl amide derivatives to synthesize a family of polycationic b-CD "click clusters" (28) bearing seven linear oligoethyleneimine branches with variable, but controlled, number of protonable amino groups (Scheme 5). [63] Agarose gel electrophoresis, DLS, and TEM experiments revealed that the click polycations complexed pDNA and protected it from nuclease degradation by forming nanoparticles with an average diameter of 80-130 nm.…”
Section: Polycationic Cyclodextrins-pdna Complexes (Cdplexes)mentioning
confidence: 99%
“…[8] The mode of binding to DNA is not known for these CDs or for other CD-based transfection agents modified on the primary side with elaborate positively charged groups. [9][10][11] The present work is an NMR spectroscopic study of the interactions of guanidino CDs with nucleic acid components, namely, the nucleotides 2Ј-deoxyadenosine 5Ј-monophosphate (5Ј-dAMP), adenosine plexes were 1:2, except for 5Ј-dAMP/bg where oligomeric aggregates formed.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, monodisperse polycationic CD conjugates with promising pDNA delivery capabilities were prepared by homogeneous functionalization of the CD primary rim (22)(23)(24). Aiming at merging the virtues of both cationic polymers and cationic lipids in a flexible, well defined framework, we have reported a modular synthetic strategy for the preparation of polycationic amphiphilic CDs (paCDs) that allows the installation of different building blocks onto either face of the truncated-cone structure in a sequential and controlled way, offering a unique opportunity for structure-activity relationship (SAR) studies (25)(26)(27) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%